Exogenously Applied Proline Enhances Morph-Physiological Responses and Yield of Drought-Stressed Maize Plants Grown Under Different Irrigation Systems - Ibrahim, Abd El-Aty; Abd El Mageed, Taia; Abohamid, Yasmin; Abdallah, Hanan; El-Saadony, Mohamed; AbuQamar, Synan; El-Tarabily, Khaled; Abdou, Nasr (Frontiers in Plant Science, 2022)
Exogenous application of osmoprotectants (e.g., proline) is an important approach to alleviate the ad-verse effects of abiotic stresses on plants. Field trials were conducted during the summer seasons of 2017 and 2018 to determine the effects of deficit irrigation combined with exogenously applied pro-line (Pro) on productivity, morph-physiological responses and yield of maize grown under two irriga-tion systems [surface irrigation (SI) and drip irrigation (DI)]. Three deficit irrigation levels (I100, I85 and I70, representing 100%, 85% and 70% of crop evapotranspiration, respectively) and two rates of Pro (Pro1=2 mM and Pro2=4 mM) were used. Plants exposed to drought stress presented a significant reduction in plant height, dry matter, leaf area, chlorophyll content (SPAD), the quantum efficiency of photosystem II (Fv/Fm, Fv/F0, and PI), water status [membrane stability index and relative water content (RWC)] and grain yield. The DI system increased crop growth and yield, and reduced irriga-tion water input by 30% compared to the SI system. Growth, plant water status and yield significant-ly decreased, as the water stress levels increased under SI conditions. Under the irrigation systems tested in this study, Pro1 and Pro2 increased plant height by 16 and 18%, RWC by 7 and 10%, mem-brane stability index by 6 and 12%, performance index by 6 and 19%, chlorophyll fluorescence by 7 and 11%, relative chlorophyll by 9 and 14% and grain yield by 10 and 14%, respectively; compared to Pro0 control treatment (no Pro). The highest grain yield (8.42 t ha-1) resulted from the interaction (I100 × Pro2) in DI. However, the exogenously applied 4 mM Pro at I85 irrigation level may be efficient un-der DI or SI system in achieving higher water productivity and yield without exerting any harmful effects on growth or yield of maize under limited water conditions. Our results demonstrated the im-portance of Pro application as a tolerance inducer of drought stress in maize plants.